The impact of emotional support on healthcare workers and students coping with COVID-19, and other SARS-CoV pandemics - a mixed-methods systematic review - Marja Härkänen; Adriana López Pineda; Susanna Tella; Sanu Mahat; Massimiliano Panella; Matteo Ratti; Kris Vanhaecht; Reinhard Strametz; Irene Carrillo; Anne Marie Rafferty; Albert W. Wu; Veli-Jukka Anttila; et al. (BMC, 2023)
Abstract Background Pandemics such as COVID-19 pose threats to the physical safety of healthcare workers and students. They can have traumatic experiences affecting their personal and professional life. Increasing rates of burnout, substance abuse, depression, and suicide among healthcare workers have already been identified, thus making mental health and psychological wellbeing of the healthcare workers a major issue. The aim of this systematic review is to synthesize the characteristics of emotional support programs and interventions targeted to healthcare workers and students since the onset of COVID-19 and other SARS-CoV pandemics and to describe the effectiveness and experiences of these programs. Method This was a mixed method systematic review. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed, and the review was registered on PROSPERO [CRD42021262837]. Searches were conducted using Medline, CINAHL, PsycINFO, Cochrane Library, and Scopus databases. The COVIDENCE systematic review management system was used for data selection and extraction by two independent reviewers. The JBI (Joanna Briggs Institute) critical appraisal tools were used to assess the quality of selected studies by two additional reviewers. Finally, data extraction and narrative analysis were conducted. Results The search retrieved 3161 results including 1061 duplicates. After screening, a total of 19 articles were included in this review. Participants in studies were nurses, physicians, other hospital staff, and undergraduate medical students mostly working on the front-line with COVID-19 patients. Publications included RCTs (n = 4), quasi-experimental studies (n = 2), cross-sectional studies (n = 6), qualitative interview studies (n = 3), and systematic reviews (n = 4). Most (63.4%) of the interventions used online or digital solutions. Interventions mostly showed good effectiveness (support-seeking, positive emotions, reduction of distress symptoms etc.) and acceptance and were experienced as helpful, but there were some conflicting results. Conclusion Healthcare organizations have developed support strategies focusing on providing emotional support for these healthcare workers and students, but it is difficult to conclude whether one program offers distinct benefit compared to the others. More research is needed to evaluate the comparative effectiveness of emotional support interventions for health workers.